2019
DOI: 10.1155/2019/3435609
|View full text |Cite
|
Sign up to set email alerts
|

A Lightweight API-Based Approach for Building Flexible Clinical NLP Systems

Abstract: Natural language processing (NLP) has become essential for secondary use of clinical data. Over the last two decades, many clinical NLP systems were developed in both academia and industry. However, nearly all existing systems are restricted to specific clinical settings mainly because they were developed for and tested with specific datasets, and they often fail to scale up. Therefore, using existing NLP systems for one’s own clinical purposes requires substantial resources and long-term time commitments for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The third article, [83], delves into the impact of intelligent speech recognition (ISR) systems on English learning, presenting a study affirming the enhancement of English listening and speaking skills among Chinese students. The article [84] [98] [100] proposes a lightweight API-based approach for flexible clinical NLP systems, aiming to simplify the development and deployment of clinical NLP systems, accompanied by a case study on adverse drug event identification. The final article [85] delves into the technical considerations of using oligonucleotide solution APIs, pivotal in synthesizing DNA or RNA strands for diverse applications, providing an extensive overview of available APIs and essential technical aspects for their use.…”
Section: Literature Surveymentioning
confidence: 99%
“…The third article, [83], delves into the impact of intelligent speech recognition (ISR) systems on English learning, presenting a study affirming the enhancement of English listening and speaking skills among Chinese students. The article [84] [98] [100] proposes a lightweight API-based approach for flexible clinical NLP systems, aiming to simplify the development and deployment of clinical NLP systems, accompanied by a case study on adverse drug event identification. The final article [85] delves into the technical considerations of using oligonucleotide solution APIs, pivotal in synthesizing DNA or RNA strands for diverse applications, providing an extensive overview of available APIs and essential technical aspects for their use.…”
Section: Literature Surveymentioning
confidence: 99%
“…Specifically, we simplify the extraction process by using the IBM Watson Natural Language Understanding API that offers sophisticated NLP techniques in extracting meta-data from content such as concepts, entities, keywords, and others. Benchmarking studies have shown that IBM Watson Natural Language Understanding API is a simple and useful NLP tool in solving various clinical NLP problems [12,13]. A demonstration of how the API works is available [14].…”
Section: Adr Extractionmentioning
confidence: 99%